SELF HEALING PADA MASA PANDEMI COVID-19: STUDI BIBLIOMETRIK - Sukaesih, Nunung Siti (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
Objective: The purpose of this study is to identify the trend and novelty of self-healing articles during the COVID-19 pandemic. Methods: The design of the study is a bibliometric study, the metadata used is published through Google Scholar, Pubmed, Scopus and Crossef. Selected articles from 2020-2022.Results: The results of the study found that there were 86 articles that examined self-healing during the COVID-19 pandemic with a total of 2020 as many as 23, in 2021 as many as 52 and 2022 as many as 12 articles. Elsevier is the largest publisher and the highest citation with 142. The productivity of the most journals is poetry therapy journals and America as the country of origin of the most self-healing journal authors by 49 authorsConclusion: Self-healing trends that are widely carried out during the COVID-19 pandemic include physical activities, reiki, worship, art therapy, resting, dancing, self-reflection, ayurveda, positive activities and training to reduce emotions. Suggestions for scientists to do research on keywords with the last cluster being self-injury.